Distal extension removable partial denture with resilient attachment connect to an anterior fixed implant-supported prosthesis: a clinical report - Zavanelli, Ricardo Alexandre; Mazaro, José Vitor Quinelli [UNESP]; Guilherme, Adérico Santana; Magalhães, Jaqueline Barbosa; Cardoso, Leandro de Carvalho; Zavanelli, Adriana Cristina [UNESP] (Jaypee Brothers Medical Publishing, 2012)
Background: Considering the limited qualitative and quantitative bone in the posterior arch, this modality of prosthetic treatment could provide a positive emotional factor reestablished by immovability of the anterior fixed implant-supported segment. Objective: This clinical report demonstrates the possibility of achieving positive results with a removable partial denture connected to an implant-supported fixed prosthesis associated to an extra resilient attachment. Clinical significance: In cases of posterior mandibular and maxilla atrophy added to the patients desire against the bone graft, this kind of prosthetic treatment has an important place as an alternative.
Keywords: Removable partial denture; Implant-supported prosthesis; Resilient attachment